Technical Feasibility of Deceit While a Vehicle is Weighed in Motion with a Very Low Speed - Zbigniew Lozia (Communications - Scientific letters of the University of Zilina, 2021)
The study concerns the problem of overloading the vehicles driven on public roads. The gross vehicle mass and individual axle loads are limited by legal regulations. However, a tricking method, applicable to most popular designs of motor vehicles and multiaxial tractor-semitrailer units, has been shown that the weighing inspectors, even if provided with precise scales, may be deceived without any interference in the scale operation. In such a method, the current vehicle state may be changed by modifying the stiffness of individual pneumatic suspension springs, which is now technically feasible. The author used two authorial vehicle models and a simulation program. Calculation results obtained for a four-axle motor vehicle and a five-axle tractor-semitrailer unit, taken as an example, have been demonstrated. They show that a deceit is possible when a vehicle is weighed in motion with a very low speed.